ANALISIS NILAI NASIONALISME DALAM NOVEL MATA DAN RAHASIA PULAU GAPI KARYA OKKY MADASARI - Sriwidayati, Eka; Hidayat, Muhamad Taufik (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
Nationalism is an attitude of love and pride for the motherland. The value of nationalism comes from the spirit of nationalism by the people to defend the country. Not only by trying to protect the land but also by being proud of the cultures. This study aimed to analyze and describe the content of nationalism values in the novel "Mata dan Rahasia Pulau Gapi". The method used in the study was content analysis with a descriptive design. The data in this study were in the form of verbal utterances, whether in the form of words, phrases, or sentences contained in the novel's text which describes the values of nationalism. Data were analyzed by data reduction, data presentation, and conclusion. The technique of assessing the validity of the data is the extension of observations and increased persistence